2008
DOI: 10.3748/wjg.14.4861
|View full text |Cite
|
Sign up to set email alerts
|

Cytokine orchestration in post-operative peritoneal adhesion formation

Abstract: Peritoneal adhesions are a near inevitable occurrence after laparotomy and a major cause of both patient and physician misery. To date, clinical attempts at their amelioration have concentrated on manipulating the physical factors that affect their development despite a wealth of experimental data elucidating the molecular mechanisms that underlie their initiation, development and maturation. However, the advent of targeted, specific anti-cytokine agents as directed therapy for inflammatory and neoplastic cond… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(20 citation statements)
references
References 80 publications
0
19
0
1
Order By: Relevance
“…Extracellular matrix (ECM) is the substance surrounding the lower layer of connective tissue of epithelial cells or endothelial cells. The ECM is one of the essential conditions for vascularization [4,5] . In our study, laminin was the main marker of ECM, which was strongly positively expressed in all rats of the control group.…”
Section: Discussionmentioning
confidence: 99%
“…Extracellular matrix (ECM) is the substance surrounding the lower layer of connective tissue of epithelial cells or endothelial cells. The ECM is one of the essential conditions for vascularization [4,5] . In our study, laminin was the main marker of ECM, which was strongly positively expressed in all rats of the control group.…”
Section: Discussionmentioning
confidence: 99%
“…From a therapeutic point of view, selectively inhibiting the cytokines involved may hold promise in preventing adhesion formation. [27][28][29][30] Omentum in Cancer and Tumorigenesis Primary tumors of the omentum are rare; however, it is a well-known site of metastases of carcinomas of the ovaries, stomach, and colon. Omentectomy is frequently performed for ovarian epithelial carcinomas as a means of staging the disease as well as to prevent local recurrence 31 and has been advocated for tumors that metastasize via the peritoneal cavity.…”
Section: Milky Spotsmentioning
confidence: 99%
“…It is also important to facilitate fibrin rich matrix deposition, necessary for cell migration and proliferation. 28,29 Also, it has been suggested that laparotomy can stimulate the for-…”
Section: Medical Students Original Articlementioning
confidence: 99%
“…Mast cells are probably not responsible for all locally released VEGF, because this cell produces cytokines that induce the influx of other inflammatory cells that could produce VEGF at the site of the lesion. 28,29 It has been shown that dexamethasone, a steroidal anti-inflammatory, in combination with sodium carboxymethylcellulose can prevent the formation of adhesions in a rat adhesion-forming model, inhibiting the migration of inflammatory cells, further decreasing the proliferation of fibroblasts. 30 Likewise, the use of non-steroidal anti-inflammatory drugs, such as Diclofenac Sodium, has been effective in decreasing adhesion formation in a model of anti-mesenteric border lesion in the rat colon.…”
Section: Original Articlementioning
confidence: 99%